


This Question is Closed

swissgirl
Best Response
You've already chosen the best response.
0
Seems to me like no solution
because if you multiply the first equation by 2 we get:
\(2(5x3y=3) \to 10x6y=6 \)

abbie1
Best Response
You've already chosen the best response.
0
Thank you! I think it's 0, but I'm not sure. I have been working on this problem forever!

swissgirl
Best Response
You've already chosen the best response.
0
hmmmmmmmmm 0 and no solution are not the same

hartnn
Best Response
You've already chosen the best response.
1
why am i getting y= 1??
and x=0.

abbie1
Best Response
You've already chosen the best response.
0
I know, but no solution isn't an option.

swissgirl
Best Response
You've already chosen the best response.
0
i cld be wrong i just did it offhandedly lol

abbie1
Best Response
You've already chosen the best response.
0
Thank you so much! it was y=1!

hartnn
Best Response
You've already chosen the best response.
1
Multiply 1st equation by 2.
10x6y=6.
subtract 2nd equation from 1st equation.
8x=0>x=0
put it in 1st equation.
3y=3>y=1
solution : (0,1)

abbie1
Best Response
You've already chosen the best response.
0
Yeah you're right! Thank you!

hartnn
Best Response
You've already chosen the best response.
1
welcome :)